Research on the Security and Defense Mechanism of Overseas Military Bases from the Dual Perspectives of “Hard Law and Soft Law” - Wang, Zhangping (International Journal of Social Sciences and Public Administration, 2024)
Legitimacy, legality and conceptual factors are vital variables that affect the security and defense mechanism of overseas military bases. Based on the resolutions of international military organizations and universal documents, international soft law coordinates the political conflicts of interests between the leasing countries of overseas military bases and the host countries, which can safeguard the “legitimacy” of overseas military bases. International hard law focuses on the “legality” of the security and defense mechanism of overseas military bases. In addition, legality requires that the acquisition and operation of overseas military bases not only comply with the constituent elements of modern international law, but also respect the domestic laws of the host country. The conceptual factor emphasizes the host country’s recognition of the base leasing country based on legitimacy and legality. Countries leasing overseas military bases need to coordinate the effectiveness of soft law and hard law based on actual conditions to build a security and defense mechanism for overseas military bases.